2022
DOI: 10.1007/s00125-022-05791-6
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness increases the risk of type 2 diabetes: a 20 year follow-up – results from the HUNT study

Abstract: Aims/hypothesis Type 2 diabetes is one of the leading causes of death globally and its incidence has increased dramatically over the last two decades. Recent research suggests that loneliness is a possible risk factor for type 2 diabetes. This 20 year follow-up study examined whether loneliness is associated with an increased risk of type 2 diabetes. As both loneliness and type 2 diabetes have been linked to depression and sleep problems, we also investigated whether any association between lonel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…In line with this nding, a previous study using data from a nationwide cohort study in Korea also identi ed living alone as a risk factor for T2D (31). Living alone may increase psychological stress and feelings of loneliness, which have been established as risk factors for T2D (32). Furthermore, living alone may lead to social isolation and result in reduced access to social and emotional support networks, which are crucial for maintaining overall health and well-being (33).…”
Section: Discussionsupporting
confidence: 56%
“…In line with this nding, a previous study using data from a nationwide cohort study in Korea also identi ed living alone as a risk factor for T2D (31). Living alone may increase psychological stress and feelings of loneliness, which have been established as risk factors for T2D (32). Furthermore, living alone may lead to social isolation and result in reduced access to social and emotional support networks, which are crucial for maintaining overall health and well-being (33).…”
Section: Discussionsupporting
confidence: 56%
“…Related to metabolic changes observed in loneliness or chronic isolation, HPA axis chronic activation leads to the elevated secretion of cortisol, increased blood glucose, glycogenolysis, and insulin resistance that ends up in engaging in unhealthy habits and decreasing satiety signaling. A recent 20-year follow-up study including 24,024 participants found that loneliness was associated with a twofold risk of type 2 diabetes in participants who informed “very much” on experiencing loneliness than those who had not felt lonely ( Henriksen et al, 2022 ).…”
Section: Part Ii: Mitochondrial Dysfunction and Its Involvement In Di...mentioning
confidence: 99%
“…A new study suggests that loneliness can double the risk of developing diabetes. 2 The study reviewed responses to health questionnaires, medical examinations, and blood samples from 24,024 people who participated in these tests between 1995 and 1997. They selected people who did not have diabetes and whose blood results were available.…”
Section: Loneliness and Diabetesmentioning
confidence: 99%